Implementasi Tri Hita Karana sebagai Upaya Kelola Mutu Taman Harmoni Bukit Asah Bugbug, Karangasem - Nyoman Ratih Prajnyani Salain; Ni Made Mitha Mahastuti (Universitas Sebelas Maret Surakarta, 2022)
Development and management are two factors that influence the existence of a tourist area. Taman Harmoni, located in the Bukit Asah area of Bugbug Village, Karangasem is an area that has been under development and management by the Bugbug Traditional Village Tourism Development Agency (BP2DAB) since 2016. The development carried out by BP2DAB is considered successful in attracting visitors to always come back. Bugbug Village realizes that the potential of nature and culture is a priceless investment and if not managed properly it will harm the lives of future generations. Not only has a negative impact on economic factors, this negligence also causes degradation of natural environmental factors and socio-cultural factors. Tri Hita Karana is one of the local wisdom that teaches about the three causes of happiness or harmony. BP2DAB makes Tri Hita Karana a concept in managing the Taman Harmoni tourist area. Elements of Tri Hita Karana will be implemented in each of the development factors carried out. The purpose of this paper is to determine the extent to which the implementation of the Tri Hita Karana concept in the management of the Taman Harmoni Bukit Asah tourism object, Bugbug Karangasem. The method used is descriptive qualitative with data collection techniques through direct observation, interviews, and literature study. The result of this paper is a form of implementation of the elements of Parahyangan, Pawongan and Palemahan in the management of the Taman Harmoni at Bukit Asah Bugbug, Karangasem.